Digitizing Lehrwerkanalyse Materials with the Flip PDF Professional Application - Dinie Dwi Putri; Primardiana Hermilia Wijayati (RIRAI Publisher, 2022)
The development of digital book using the Flip PDF Professional application for Lehrwerkanalyse course is motivated by the lack of interactive teaching materials for students. The aims of this research are: (1) to develop a digital book for Lehrwerkanalyse course through the Flip PDF Professional application; (2) to determine the feasibility of digital books based on expert judgment and student perceptions. This research is a research and development (R&D) using the ADDIE development model. This research was tested on students of German Language Education Study Program, Universitas Negeri Malang. The stages of this research are: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The data collection method used a questionnaire to obtain assessment data from students on the product. The result of the product is an OFFEN digital book contains 8 materials presented in the form of text, video, audio, supporting images, mini quizzes, and essay assignments for the Lehrwerkanalyse course. The results of the expert assessment using the Gregory validity formula, the feasibility is at a score of 0.96 (very high). The implementation of digital book for students results in that these digital books have an attractive appearance, easier to understand the material, can be used as independent teaching materials, and is easy to access. Based on these two assessments, the OFFEN digital book is suitable to use as independent teaching material.